2020
DOI: 10.1002/ece3.6334
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic analyses reveal distinct population structures and ecotypes for sugar beet‐associated Pseudomonas in Oxford and Auckland

Abstract: Fluorescent pseudomonads represent one of the largest groups of bacteria inhabiting the surfaces of plants, but their genetic composition in planta is poorly understood. Here, we examined the population structure and diversity of fluorescent pseudomonads isolated from sugar beet grown at two geographic locations (Oxford, United Kingdom and Auckland, New Zealand). To seek evidence for niche adaptation, bacteria were sampled from three types of leaves (immature, mature, and senescent) and then characterized usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Measurement of the amount of pyoverdin in cells that localize the iron chelator showed that it is the same as that Polarization test in natural isolates, left to right and top to bottom: U106 (liquid KB medium for 24 h); U177 (SMM agarose pad for 24 h); U149 (liquid SMM with DP 100 µg/ml for 24 h); U180 (liquid SMM with DP 100 µg/ml for 24 h); U181 (SMM agarose pad for 16 h); T24 V1a (SMM agarose pad for 24 h); T24 V9b (SMM agarose pad for 24 h); T24 H1b (SMM agarose pad for 24 h); T24 H9b (liquid SMM for 24 h). Natural isolates were collected in Oxford, UK [33] (first and second row) and in Paris, France [32] (Bottom row)(locations are roughly marked with a pink circle on the map). Color represents the identified Pseudomonas species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of the amount of pyoverdin in cells that localize the iron chelator showed that it is the same as that Polarization test in natural isolates, left to right and top to bottom: U106 (liquid KB medium for 24 h); U177 (SMM agarose pad for 24 h); U149 (liquid SMM with DP 100 µg/ml for 24 h); U180 (liquid SMM with DP 100 µg/ml for 24 h); U181 (SMM agarose pad for 16 h); T24 V1a (SMM agarose pad for 24 h); T24 V9b (SMM agarose pad for 24 h); T24 H1b (SMM agarose pad for 24 h); T24 H9b (liquid SMM for 24 h). Natural isolates were collected in Oxford, UK [33] (first and second row) and in Paris, France [32] (Bottom row)(locations are roughly marked with a pink circle on the map). Color represents the identified Pseudomonas species.…”
Section: Discussionmentioning
confidence: 99%
“…Paris, France [32]: T24 V1a, T24 V9b, T24 H1b, T24H9b; all classified as P. putida . Oxford, UK [33]: P. marginalis U106, P. putida U177, P . aureofaciens U149, U180, and U181.…”
Section: Methodsmentioning
confidence: 99%